Reinforcement learning based multi core scheduling (RLBMCS) for real time systems - Dhruva R. Rinku; M. AshaRani (Institute of Advanced Engineering and Science, 2020)
Embedded systems with multi core processors are increasingly popular because of the diversity of applications that can be run on it. In this work, a reinforcement learning based scheduling method is proposed to handle the real time tasks in multi core systems with effective CPU usage and lower response time. The priority of the tasks is varied dynamically to ensure fairness with reinforcement learning based priority assignment and Multi Core MultiLevel Feedback queue (MCMLFQ) to manage the task execution in multi core system.